Historical Basis Confirming Signs of the Existence of “Meokhi”-Lawyer ın Feudal Georgia - Nugzar Birkaia (European Scientific Journal, ESJ, 2017)
The article discusses historical basis confirming signs of existence “Meokhi” (intercessor, advocate, protector) in feudal Georgia that certainly, has its reasons. History of advocacy is an important integral part of any country’s legal culture. “Meokhi’’ that stands for intercessor in Georgian or the words of foreign origin – Arabic “vekili” or Latin advocate were used to denote a “defender” in Georgian legislation. Lawyer’s profession counts several thousand years. Presumably, there were layers of the society bearing this profession in feudal Georgia which is directly or indirectly confirmed by Georgian literary sources and the fundamental researches. Advocacy originated in the ancient era. Lawyer’s profession was considered as a free and honorable profession in ancient Rome. It is a well-known fact that in the Roman Empire qualified lawyers were selected to make explanations at the court. 74 It is noteworthy that in the period of unification of Georgia, in the 11-12 centuries, law specialists were “scholars of the assembly’’, who were invited to the court and there is a high probability that they participated in the processes.75 We want to prove that in the united Georgia there was a layer of the society which had the function of “meokhi” – representatives of parties who actually provided defense. We believe that all this, as a historical reality, will be interesting for individuals who work in this profession, lawyers, and generally, for the whole society.